Palaces of hope : the anthropology of global organizations - Niezen, Ronald; Sapignoli, Maria (Cambridge : Cambridge University Press, 2017)
This volume assembles in one place the work of scholars who are making key contributions to a new approach to the United Nations, and to global organizations and international law more generally. Anthropology has in recent years taken on global organizations as a legitimate source of its subject matter. The research that is being done in this field gives a human face to these world-reforming institutions. Palaces of Hope demonstrates that these institutions are not monolithic or uniform, even though loosely connected by a common organizational network. They vary above all in their powers and forms of public engagement. Yet there are common threads that run through the studies included here: the actions of global institutions in practice, everyday forms of hope and their frustration, and the will to improve confronted with the realities of nationalism, neoliberalism, and the structures of international power.
Machine generated contents note: 1. Introduction Ronald Niezen and Maria Sapignoli; 2. Heart of darkness: an exploration of the WTO Marc Abeles; 3. Horseshoe and catwalk: power, complexity and consensus-making in the United Nations Security Council Niels Nagelhus Schia; 4. A kaleidoscopic institutional form: expertise and transformation in the permanent forum on indigenous issues Maria Sapignoli; 5. The'public' character of the Universal Periodic Review: contested concept and methodological challenge Jane K. Cowan and Julie Billaud; 6. Meeting'the world' at the Palais Wilson: embodied universalism at the UN Human Rights Committee Miia Halme-Tuomisaari; 7. Expertise and quantification in global institutions Sally Engle Merry; 8. From boardrooms to field programs: humanitarianism and international development in Southern Africa Robert K. Hitchcock; 9. Global village courts: international organizations and the bureaucratization of rural justice systems in the Global South Tobias Berger; 10. Contrasting values of forests and ice in the making of a global climate agreement Noor Johnson and David Rojas; 11. The best of the best: positing, measuring and sensing value in the UNESCO World Heritage Arena Christoph Brumann; 12. Propaganda on trial: structural fragility and the epistemology of international legal institutions Richard Ashby Wilson; 13. The anthropology by organizations: legal knowledge and the UN's ethnological imagination Ronald Niezen; Index.
Title from publisher's bibliographic system (viewed on 28 Feb 2017).
Keywords: Law and anthropology; International organizations